2017
DOI: 10.1186/s40792-017-0311-5
|View full text |Cite
|
Sign up to set email alerts
|

Solitary choroidal metastasis from gastric adenocarcinoma: a case report

Abstract: BackgroundMetastatic choroidal carcinomas that originated from the gastrointestinal tract are extremely rare. We report a case of suspected solitary choroidal metastasis from gastric adenocarcinoma.Case presentationThe patient was a 60-year-old man who had undergone laparoscopic distal gastrectomy with D1+ lymphadenecetomy for gastric cancer. The clinical stage was T1bN0M0 (TNM classification), but the pathological stage was T4aN0M0 beyond expectation. Adjuvant chemotherapy with oral Tegafur, Gimeracil, Oterac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The patients with choroidal metastasis have a poor prognosis. [26,27] The reported cases with choroidal metastasis from GC had survival durations of 9 months [16] and 3 years, [15] and our patient died 8 months after the first diagnosis of choroidal metastasis. Poor response to chemotherapy and long duration of choroidal metastasis from GC may have led to spontaneous rupture of the eyeball.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The patients with choroidal metastasis have a poor prognosis. [26,27] The reported cases with choroidal metastasis from GC had survival durations of 9 months [16] and 3 years, [15] and our patient died 8 months after the first diagnosis of choroidal metastasis. Poor response to chemotherapy and long duration of choroidal metastasis from GC may have led to spontaneous rupture of the eyeball.…”
Section: Discussionmentioning
confidence: 84%
“…[1,9] However, systemic chemotherapy is commonly used for choroidal metastasis from GC as it is insensitive to radiotherapy. [3] A combination of systemic paclitaxel and local intensity-modulated radiotherapy provided remission in a case of choroidal metastasis from GC, [15] while chemotherapy with oral S-1 and intravenous cisplatin reduced choroidal lesions in another case. [7] However, choroidal metastasis from GC was found to be resistant to systemic imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…From a review of published studies between 2011 and 2019, we identified only five other case reports of choroidal metastases from GC (Table 1). [13][14][15][16][17] Two reports were from Japan, and one each from China, Korea and Nepal. Four patients were male and one female and ages ranged from 40 to 75 years.…”
Section: Discussionmentioning
confidence: 99%
“…Intraocular malignancy is a rare disease and is most commonly caused bymetastatic tumors [3] . Choroidal metastatic tumors from malignancies in the gastrointestinal tract are extremely rare compared with the more common metastatic breast and pulmonary carcinomas [9] . Nevertheless, metastatic tumors in the orbit account for only 2-3% of all systemic cancers.…”
Section: Discussionmentioning
confidence: 99%